346 Bivalirudin use during continuous renal replacement therapy in a 2.5-year-old girl suffering from cardiomyopathy and receiving VAD support. (11th October 2021) - Matković, Hana; Slaviček, Jasna; Rubić, Filip; Dessardo, Sandro; Cvitković, Miran; Matić, Toni; Bartoniček, Dorotea; Belina, Dražen; Kos, Ivanka; Galić, Slobodan
Abstract : Ventricle assist devices (VAD) are often the only bridge to heart transplantation in children with deteriorating cardiomyopathies. Berlin Heart EXCOR Pediatric is registered for children and can be used to support the function of right, left or both ventricles. Despite the use of the 'Edmonton protocol' to guide the anticoagulation management, thromboembolism and hemorrhage are common adverse effects. Moreover, prolonged intravenous heparin use is often complicated with heparin induced thrombocytopenia (HIT), which leads to a conclusion that new antithrombotic strategies are needed, such as use of direct inhibitor of thrombin, i.e. bivalirudin. In our patient, a 2.5-year-old girl with restrictive cardiomyopathy, heart decompensation occurred after a viral infection (with later confirmation of parvovirus B19 myocarditis). Mechanical circulatory support with VA ECMO was started, with an implantation of LVAD Berlin Heart 3 weeks later. She spent 125 days on VAD support waiting for a heart transplantation. The 'Edmonton protocol' was followed for anticoagulation and anti-aggregation therapy guidance (warfarin, acetylsalicylic acid and clopidogrel). She suffered multiple complications: bilateral pleural effusions, middle cerebral artery thrombosis, fibrin over the VAD cannula, intracranial hemorrhage and shunt meningitis. During an episode of septic shock, acute renal failure occurred, requiring continuous veno-venous hemodiafiltration that has been continued for 21 days. Prolonged thrombocytopenia led to diagnosis of HIT, so heparin was replaced with bivalirudin (direct thrombin inhibitor) as anticoagulation therapy, in addition to acetylsalicylic acid and clopidogrel. Bivalirudin use is easily monitored by APTT and ACT and the dosage is modified according to it. Bivalirudin has been used for 16 days along with CVVHDF, without hemofilter occlusion or fibrin deposits on cannulas of BH Excor. According to our experience and cases described in literature, bivalirudin has been used in children with VAD Berlin Heart EXCOR with positive outcomes. In addition, successful use of bivalirudin for anticoagulation during continuous renal replacement was associated with longer hemofilter survival time and less hemorrhagic and/or thrombotic events. On the other hand, there are some disadvantages such as lack of pediatric experience, no available antidote and high price. From all of the above, we may conclude that new experiences and investigations are needed and alternative anti-thrombotic drugs, such as bivalirudin, should be considered for patients with VAD and CVVHDF.